''Pegadas'' históricas: educação de pessoas trabalhadoras no Distrito Federal (1957 a 1998) - Oliveira, Leila Maria de Jesus (2022)
This thesis is linked to the line of research on "Work, Education and Social Movements" of the Post-Graduation Program in Education, at the Education College of the Federal University of Goias, and its theme is the education of youth and the adult working class in the Federal District, from the period of 1957 to 1998. The general goal of the research was to historically identify the initiatives to meet the demand for education of young and adult working people in the Federal District, to bring reflection about the granted right to education for the popular classes. In order to reach this goal, we carried out a historiographic, investigative, documental, and bibliographic research, of the qualitative sort. We relied on testimonies from people involved with education in the Federal District. The historical reconstitution of this research allowed us to present in three chapters, in an unprecedented manner, the trajectory of the area of education of young and adult working citizens in the federal capital, by elucidating the political-administrative conjuncture of the Federal District and its approximations with what happens in the national scenario; the organization and political participation of civil society; the district and national legislation in the field of youth and adult education; the characteristics of the growing population of the Federal District; the survey of demand and enrollment, as well as the organization and supply of the public school system and of popular movements for the education of young people and adults, attempting to apprehend the organization of this supply, in the scope of the political and civil society, in a conception of an Integral State. We found that, although a set of initiatives is perceptible, from the political society, as well as from the civil society, in favor of the education of the young and adult working class in the Federal District, this movement, throughout history, did not ensure the access, permanence, and continuity of a full education to these individuals. Beyond the initiatives elucidated, the research reveals that the offer of this education remains a disputed field, where, on one hand we see the stigmas of young and adult education revealed in the permanent class disputes, in the prevalence of capital interests over the formation of the working class, and in the work relations with the working force who built Brasilia, and, on the other hand, the persistent concern of social movements that have as their agenda the elevation of schooling for this demographic, understanding it as fundamental for the emancipation of these people, and the construction of a fair and egalitarian society.